Examining The Effects Of Consumer E-Service Quality And E-Satisfaction On Consumer Behavioural Intention In Malaysia: A Case Study On Online Shopping - Lee, Yeh Weng (2010)
Online shopping had established a new market opportunity in the global market and research had foreseen a steady trend of growth on online shopping in the Asia/Pacific region. Numerous studies and researches have been conducted to evaluate the online shopping behaviour around the world; however there is still a lack of study in pertaining to each country individually. It is inevitable to study the behaviour of online shopping individually as the behaviour for each country’s online shopper may deviate significantly due to the difference in culture, religion, infrastructure development and income level. In this research, the dimension of e-service quality and e-satisfaction had been used in the determination of the online shopping consumer behavioural intention in the Malaysia context. A research framework had been created in reference to four major literature frameworks. i.e. Cronin et al (2000), Parasuraman et al (2005), Liu et al (2008) and Zeithaml et al (1996). A quantitative approach had been carried out in this research; a sample size of 150 respondents had been collected from the population in Malaysia through online survey and personal interview. A non parametric test of descriptive statistic analysis was performed, followed by inferential parametric tests of reliability analysis, exploratory factor analysis and regression analysis by the use of SPSS analysis software on the received data. The result of the analysis confirmed the significant causal relationship between e-service quality, e-satisfaction and behavioural intention. All determinant variables were also found to be correlated with each relevant dimension. Malaysian online shoppers were relatively associated with younger age group, well educated and middle-income segment consumers. Malaysia online consumers preferred to have a high level of e-service quality and esatisfaction performance from the online retailer. However in general, the overall findings have demonstrated that Malaysia online consumers are still reacting negatively towards the purchasing intention of online shopping. Security concern remains the biggest challenge for the online retailing industry. The research outcome had enlightened a number of insights towards the behavioural intention and their influence variables pertaining to the online shopping within Malaysia. It had enabled online retailer to steer their business in the right direction by meeting consumers’ desired-service levels.